Macroeconomic Determinants of Households’ Indebtedness in Portugal: What Really Matters in the Era of Financialisation? - Romão, A.; Barradas, R. (Dinâmia’CET-IUL Working Paper Nº 2020/06, 2020)
The objective of this paper is to perform a time series econometric analysis in order to empirically assess the macroeconomic determinants and the corresponding drivers of the Portuguese households’ indebtedness in the period 1988 to 2016. During that period, the Portuguese economy experienced a process of financialisation that contributed to an increase in Portuguese households’ indebtedness to unprecedented levels. The Portuguese households’ indebtedness played a crucial role in the recent sovereign debt crisis. Based on the existing literature, we hypothesize that Portuguese households’ indebtedness was due to seven macroeconomic determinants, notably housing prices, financial asset prices, the degree of personal income inequality, households’ labour income, the importance of welfare state expenditures, the fraction of the working-age population and the level of interest rates. Our findings reveal that financial asset prices, the degree of personal income inequality, households’ labour income and the fraction of the working-age population positively impact Portuguese households’ indebtedness, whereas the housing prices negatively impact Portuguese households’ indebtedness. Our findings also show that the increase in financial asset prices and the decline in housing prices were the main drivers of Portuguese households’ indebtedness in the last few decades.